(untitled) - Soseki, Natsume (Tokyo, 1972)
Botchan, like The Adventures of Huckleberry Finn or The Catcher in the Rye, is a classic of its kind, a sly, funny, poignant tale about a young mans rebellion against the system. Since its original publication 100 years ago, it has enjoyed a timeless popularity among Japanese readers both young and old, making it, according to Donald Keene, probably the most widely read novel in modern Japan.
Keywords: Japanese literature,Japan; Fiction